ABSOLUTE EQUIVALENCE OF PHRASEOLOGISMS WITH THE COMPONENT EYE IN ITALIAN, SPANISH AND SERBIAN - Marija N. Vujović (Filolog, 2023)
This paper deals with a contrastive and conceptual analysis of somatic phraseologisms with the component eye in Italian, Spanish and Serbian, with the aim to find absolute cross-linguistic equivalents, i.e. those phraseologisms that will show a perfect symmetry on the semantic, formal and functional level, but also congruence in the concepts they express. A corpus of 102 phraseologisms was excerpted from the relevant general and phraseological dictionaries. The initial hypothesis is that, despite the fact that cases of absolute equivalents are rare, the analysed corpus will offer a significant number of such phraseologisms since somatic phraseology, due to the universality of bodily experience, reveals analogies between languages. The corpus was first subjected to a contrastive analysis in order to identify the cases of absolute equivalents. The corpus was also subjected to conceptual analysis, that aimed at determining the motivational mechanism underlying the phraseologisms, thanks to the postulated conceptual metaphors and metonymies, and then the phraseologisms were classified into semantic fields. The results confirmed the initial hypothesis. The phraseological corpus of the three contrasted languages offers a significant number of absolute translation equivalents among phraseologisms with the component eye. The largest number of absolute equivalents belongs to the semantic fields INSIGHT (6), followed by LOVE and ATTENTION/CAUTION (5). The first case can be explained by the fact that in almost all linguistic and cultural communities, eyes symbolise intellectual perception, and the second, that the semantic field of LOVE does not have precisely defined boundaries and implies different feelings ranging, from liking to lust. In the case of ATTENTION/CAUTION, the eyes, as the most important sense that perceives almost 90% of information serve, among other things, to monitor a situation and keep it under control. Some phraseologisms owe their absolute equivalence to the Bible, classical literature or mythology, and some to polygenesis and calques.